Susceptibility to the pinewood nematode (PWN) of four pine species involved in potential range expansion across Europe - Nunes da Silva, Marta; Solla, Alejandro; Sampedro, Luis; Zas, Rafael; Vasconcelos, Marta W. (Tree physiology, 2015)
The pine wilt disease (PWD), caused by the pinewood nematode (PWN) Bursaphelenchus xylophilus (Steiner et Buhrer) Nickle, is one of the most serious threats to pine forests worldwide. Here we studied several components of susceptibility to PWN infection in a model group of pine species widely distributed in Europe (Pinus pinaster Ait., P. pinea L., P. sylvestris L. and P. radiata D. Don), specifically concerning anatomical and chemical traits putatively related to nematode resistance, whole-plant nematode population after experimental inoculation, and several biochemical and physiological traits indicative of plant performance, damage and defensive responses 60 days post inoculation (dpi) in 3-year-old plants. Pinus pinaster was the most susceptible species to PWN colonization, with a 13-fold increase in nematode population size following inoculation, showing up to 35-fold more nematodes than the other species. Pinus pinea was the most resistant species, with an extremely reduced nematode population 60 dpi. Axial resin canals were significantly wider in P. pinaster than in the other species, which may have facilitated nematode dispersal through the stem and contributed to its high susceptibility; nevertheless, this trait does not seem to fully determinate the susceptible character of a species, as P. sylvestris showed similar nematode migration rates to P. pinaster but narrower axial resin canals. Nematode inoculation significantly affected stem water content and polyphenolic concentration, and leaf chlorophyll and lipid peroxidation in all species. In general, P. pinaster and P. sylvestris showed similar chemical responses after infection, whereas P. radiata, which co-exists with the PWN in its native range, showed some degree of tolerance to the nematode. This work provides evidence that the complex interactions between B. xylophilus and its hosts are species-specific, with P. pinaster showing a strong susceptibility to the pathogen, P. pinea being the most tolerant species, and P. sylvestris and P. radiata having a moderate susceptibility, apparently through distinct coping mechanisms.